Overview of mechanisms and novel therapies on rheumatoid arthritis from a cellular perspective - Han, Peng; Liu, Xiaoying; He, Jiang; Han, Luyang; Li, Jinyao (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovial inflammation of joints in response to autoimmune disorders. Once triggered, many factors were involved in the development of RA, including both cellular factors like osteoclasts, synovial fibroblasts, T cells, B cells, and soluble factors like interleukin-1 (IL-1), IL-6, IL-17 and tumor necrosis factor-α (TNF-α), etc. The complex interplay of those factors results in such pathological abnormality as synovial hyperplasia, bone injury and multi-joint inflammation. To treat this chronic life-affecting disease, the primary drugs used in easing the patient's symptoms are diseasemodifying antirheumatic drugs (DMARDs). However, these traditional drugs could cause serious side effects, such as high blood pressure and stomach ulcers. Interestingly, recent discoveries on the pathogenesis of RA have led to various new kinds of drugs or therapeutic strategies. Therefore, we present a timely review of the latest development in this field, focusing on the cellular aspects of RA pathogenesis and new therapeutic methods in clinical application. Hopefully it can provide translational guide to the pre-clinical research and treatment for the autoimmune joint disease.